Casino Royale - Fleming, Ian, 1908-1964 (Fleming, Ian, 1908-1964. James Bond 007, 2012)
British secret agent James Bond takes on "Le Chiffre", a lethal Soviet operative with a weakness for gambling. Bond's mission is to bankrupt Le Chiffre at the baccarat table so Moscow will kill him to avoid further embarrassment.